Active civic participation of immigrants in Portugal - Teixeira, Ana (2005)
Portugal’s historical past strongly influences the composition of the country’s immigrant population. The main third-country foreign nationals in Portugal originate traditionally from Portuguese-speaking African countries (namely Cape Verde, Angola, Guinea Bissau, and S. Tomé e Príncipe) and Brazil. In 2001, a newly created immigrant status entitled “permanence” authorization uncovered a quantitative and a qualitative change in the structure of immigrant population in Portugal. First, there was a quantitative jump from 223.602 foreigners in 2001 to 364.203 regularized foreigners in 2003. Secondly, there was a substantial qualitative shift in the composition of immigrants. The majority of the new immigrants began coming from Eastern European countries, such as Ukraine, Moldavia, Romania, and the Russian Federation. Thus, European countries outside the E.U. zone now rank second (after African countries) in their contribution of individuals to the stocks of immigrant population in Portugal. The differences between the new and traditional immigration flows are visible in the geographical distribution of immigrants and in their insertion into the labour market. While the traditional flows would congregate around the metropolitan area of Lisbon and in the Algarve, the new migratory flows tend to be more geographically dispersed and present in less urbanized areas of Portugal. In terms of insertion in the labour market, although the construction sector is still the most important industry for immigrant labour, Eastern European workers may also be found in the agriculture and manufacturing sectors. The institutional conditions that encourage immigrants’ civic participation are divided at three different levels: the state, the local, and the civil society levels. At the state level, the High Commissioner for Migrations and Ethnic Minorities is the main organizational structure along with a set of interrelated initiatives operating under specific regulatory frameworks, which act as mediators between state officials and the Portuguese civil society, and more specifically, immigrant communities. At the local level, some municipalities created consultative councils and municipal departments aiming at encouraging the participation and representation of interests from immigrant groups and association in local policies. In the civil society sphere, the main actors in Portugal spurring immigrants civic participation are immigrant associations, mainstream associations directed toward immigration topics, and unions. The legal conditions framing immigrants’ access to social housing, education, health, and social security in Portugal are also considered to be positive. Conditions restricting immigrants’ civic participation are mainly normative and include the Portuguese nationality law, the regulations shaping the political participation of immigrants, namely in what concerns their right to vote, and employment regulations restricting immigrants’ access to public administration positions. Part II of the report focuses on the active civic participation of third country immigrants. First, reasons for the lack of research on this issue in Portugal are explained. On the one hand, the recent immigration history and the more urgent needs regarding school and economic integration kept this issue out of the research spotlight. On the other hand, it was just in the beginning of the 1990s that immigrants took the very first steps toward collective mobilisation. Secondly, the literature review of Portuguese bibliography covers research on third country immigrants’ associative movement, research on local authorities’ policies and discussion about ethnic politics and political mobilisation of immigrants in Portugal. As political mobilisation of these groups has been made mainly through ethnic and/or migrant organisations, a brief history of immigrants' associative movement is given. Immigrant associations develop multiple roles, covering the social, the cultural, the economic and the political domains. Political claiming for the regularisation of illegal immigrants has been a permanent and important field of intervention since the mid-1990s. Research results reveal the com5 plex relations between ethnic mobilisation and the set of legal and institutional frameworks developed by local and national governmental authorities targeted to the incorporation of minority groups. Case studies on the Oeiras district and on the Amadora district are then presented. Conclusions underline that the most active immigrant groups are those from Cape Verde and Guinea Bissau, since these groups have constituted a higher number of ethnic associations, give priority to political claiming and present a more politicised discourse. Reflecting on the future of research on civic participation of third country immigrants in Portugal, the authors state that it would be interesting and relevant to compare the Portuguese situation with those of other European countries, with an older immigration history, and analyse how the Portuguese immigrants’ associative movement will be affected by a changing legal framework and the emergence of new opportunities within the set of structures regarding the political participation of minority groups.